1992
DOI: 10.1002/j.1552-4604.1992.tb04636.x
|View full text |Cite
|
Sign up to set email alerts
|

Dr. N‐Acetylation Polymorphism and Diabetes Mellitus among Saudi Arabians

Abstract: The acetylator phenotypes of 200 Saudi diabetics and an equal number of control subjects of the same origin were determined by measuring the peak height ratio of two urinary caffeine metabolites, 5-acetylamino-6-formylamino-3-methyluracil (AFMU) and 1-methylxanthine (1MX), using a simplified high-performance liquid chromatographic method. Urine samples were collected from the diabetics and the control subjects who regularly drink coffee, tea, or caffeinated beverages as part of their normal daily diet. The pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Populations numbered from 1 to 13 were analyzed in this study: (1) Bakola Pygmies, (2) Baka Pygmies, (3) Ateke Bantus, (4) Somali, (5) Morrocans, (6) Ashkenazi Jews, (7) Sardinians, (8) Swedes, (9) Saami, (10) Turkmen, (11) Gujarati, (12) Thai, and (13) Chinese. Numbers 14 to 36 refer to a reviewed population: (14) Yorubas (Jeyakumar and French 1981), (15) Zimbabweans (Nhachi 1988), (16) South Africans (Hodgkin et al 1979), 17Libyans (Karim et al 1981), (18) Saudi Arabians (El-Yazigi et al 1992), (19) Emiratis (Woolhouse et al 1997), 20Iranians (Sardas et al 1993), (21) Jordanians (Irshaid et al 1992), (22) Turkmen (Bozkurt et al 1990), (23) Greeks (Asprodini et al 1998), (24) Germans (Cascorbi et al 1995), (25) Russians (Lil'in et al 1984), (26) Pakistanis (Saleem et al 1989), (27) Bangladeshi (Zaid et al 2004), (28) Thai (Kukongviriyapan et al 1984), (29) Malaysians (Ong et al 1990), (30) Chinese (Zhao et al 2000), (31) Koreans (Lee et al 2002), (32) Japanese (Hashiguchi and Ebihara 1992), (33) Papua New Guineans (Hombhanje 1990), (34) Australian Aborigines (Ilett et al 1993), (35) Eskimos (Eidus et al 1974), and (36) Amerindians (Jorge-Nebert et al 2002).…”
Section: Figurementioning
confidence: 99%
“…Populations numbered from 1 to 13 were analyzed in this study: (1) Bakola Pygmies, (2) Baka Pygmies, (3) Ateke Bantus, (4) Somali, (5) Morrocans, (6) Ashkenazi Jews, (7) Sardinians, (8) Swedes, (9) Saami, (10) Turkmen, (11) Gujarati, (12) Thai, and (13) Chinese. Numbers 14 to 36 refer to a reviewed population: (14) Yorubas (Jeyakumar and French 1981), (15) Zimbabweans (Nhachi 1988), (16) South Africans (Hodgkin et al 1979), 17Libyans (Karim et al 1981), (18) Saudi Arabians (El-Yazigi et al 1992), (19) Emiratis (Woolhouse et al 1997), 20Iranians (Sardas et al 1993), (21) Jordanians (Irshaid et al 1992), (22) Turkmen (Bozkurt et al 1990), (23) Greeks (Asprodini et al 1998), (24) Germans (Cascorbi et al 1995), (25) Russians (Lil'in et al 1984), (26) Pakistanis (Saleem et al 1989), (27) Bangladeshi (Zaid et al 2004), (28) Thai (Kukongviriyapan et al 1984), (29) Malaysians (Ong et al 1990), (30) Chinese (Zhao et al 2000), (31) Koreans (Lee et al 2002), (32) Japanese (Hashiguchi and Ebihara 1992), (33) Papua New Guineans (Hombhanje 1990), (34) Australian Aborigines (Ilett et al 1993), (35) Eskimos (Eidus et al 1974), and (36) Amerindians (Jorge-Nebert et al 2002).…”
Section: Figurementioning
confidence: 99%
“…This comes as no sur prise since this enzyme has been employed to deter mine the ace ty la tion phe no type of the indi vid ual (i.e., fast or slow ace ty la tor), which is known to be influ enced by the genetic con sti tu tion of the indi vidual and by vari ous dis eases other than those of the liver (i.e., dia be tes mel li tus, blad der can cer, etc.). 28,29 Although there was no sig nifi cant dif fer ence in the uri nary molar ratio of 1U/1X that reflects the activ ity of XO 4,21,22,30 between LD patients and con trols, the mean value observed in the patients was twice that in the con trol sub ject (Table II). This sug gests no or a slight link between XO and LD.…”
Section: Discussionmentioning
confidence: 91%
“…The majority of the studies investigating the acetylator phenotype in type 2 DM also suggested a possible excess of rapid acetylators [45,46,[51][52][53][54], but this difference was less striking than that reported in phenotyping studies of type I DM previously cited, and it was not found in Arabian populations [55][56][57]. On the contrary, Agúndez et al [58], in their genotype analysis of 111 patients with type 2 DM, found no relationship between NAT2 polymorphism and type 2 DM.…”
Section: Diabetes Mellitus (Dm)mentioning
confidence: 90%